Using Center Learning in Building Early Childhood Character - Ardin, Hani Septiani; Syafril, Syafrimen (Universitas Islam Negeri Raden Intan Lampung, 2021)
Building children's character from an early age is important, because children's character is the main key to developing quality resources. One of the problems that is often encountered in building early childhood character is the use of learning methods that are not suitable for early childhood development. One of the learning methods that are suitable for early childhood development is the center learning method. Building the character of early childhood during the pandemic Covid-19 is a new challenge for teachers, because learning is done online. However, using face-to-face learning center learning methods can be done virtually by utilizing technology. Based on the analysis carried out from 98 scientific articles published in various reputable journals in various countries (Japan, Europe, Korea, China, India, Australia, England and Indonesia), it was found that center learning can be used as an alternative to help teachers build character. early childhood. Central learning is assumed to be in accordance with early childhood development which emphasizes the principle of learning while playing. For this reason, center learning can be an option for teachers in the learning process, especially in building early childhood character. In fact, teachers need to be given special skills related to how to apply this learning center, so that the process of character building for early childhood can still be done even though face-to-face learning is done virtually.